Bismuth ferrite-lead titanate-barium titanate ternary system high-temperature piezoelectric ceramic material as well as preparation method and application thereof

By introducing titanate and rare earth elements in high-temperature piezoelectric ceramic materials, the formation of iron-titanium-lead-titanate-titanate titanate triple material, solving existing high-temperature voltage ceramic materials at high temperatures at high temperature. The problem of attenuation achieves high -efficiency and low -cost high -temperature voltage performance.

CN119330697APending Publication Date: 2025-01-21SHANGHAI UNIV +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411448025.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

Smart Images

  • Figure CN119330697A_ABST
    Figure CN119330697A_ABST
Patent Text Reader

Abstract

The invention relates to a bismuth ferrite-lead titanate-barium titanate ternary system high-temperature piezoelectric ceramic material and a preparation method and application thereof, the bismuth ferrite-lead titanate-barium titanate ternary system high-temperature piezoelectric ceramic material has a chemical general formula of (1-x-y) (BiMez) FeO3-xPbTiO3-yBaTiO3, Me is a rare earth element, x is equal to 0.13-0.27, y is equal to 0.10-0.25, z is equal to 0-0.30, and z is not 0. Me is selected from any one of La, Ce, Sm, Gd and Ho. Compared with the prior art, due to the introduction of Me, the weakening of the covalent characteristic of a B-O bond and the promotion of domain rotation, the excellent piezoelectric property is obtained while the high Curie temperature is ensured, the leakage conductance is reduced through ion doping, and the application of the piezoelectric material in devices is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of piezoelectric ceramic materials, and in particular to a bismuth ferrite-lead titanate-barium titanate ternary high-temperature piezoelectric ceramic material and a preparation method and application thereof. Background Art

[0002] Piezoelectric ceramic materials are electronic functional materials that can realize the mutual conversion of electrical energy and mechanical energy. Various piezoelectric components constructed of piezoelectric ceramic materials (such as knock sensors, acceleration sensors, acoustic wave detectors, etc.) are widely used in many fields in high-temperature environments, such as automobile alarms, aerospace, and oil exploration. As the core component of piezoelectric components, the performance parameters of piezoelectric ceramic materials, especially high-temperature piezoelectric performance and Curie temperature, directly determine the performance of the device. In order to meet the needs of high-temperature applications, piezoelectric materials with high Curie temperatures must be selected to ensure that piezoelectric devices can work normally and stably in a wide temperature range.

[0003] At present, the most mature commercial lead zirconate titanate (PZT) based piezoelectric ceramics have a rapid attenuation of piezoelectric performance and device failure when the Curie temperature is above half (150°C). Although high-temperature piezoelectric single crystal materials have good piezoelectric performance and stability, they have complex processes and high production costs, which limit their application in high-temperature environments. Therefore, people have long been committed to developing low-cost, high-performance and temperature-stable high-temperature piezoelectric ceramic materials.

[0004] Perovskite ferroelectric BiFeO3-PbTiO3 (BF-PT) has attracted widespread attention for its excellent theoretical piezoelectric properties and Curie temperature (650℃) much higher than that of PZT ceramics. Although BF-PT has a good prospect, the internal strain caused by large internal stress and large tetragonal distortion are found in the actual preparation and application process, which limits its practical application. In addition, BF-PT ceramics have a large coercive field (~100kV / cm) and poor insulation properties (~10 9 Ω.cm), which makes it difficult to polarize the sample. During the preparation process, Fe ions are prone to change valence (Fe 3+ →Fe 2+ ) causes its leakage conductance to be large, making it difficult to characterize the piezoelectric performance. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a bismuth ferrite-lead titanate-barium titanate ternary high-temperature piezoelectric ceramic material and its preparation method and application.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] One of the technical solutions of the present invention is to provide a bismuth ferrite-lead titanate-barium titanate ternary high temperature piezoelectric ceramic material.

[0008] The general chemical formula of the bismuth ferrite-lead titanate-barium titanate ternary high temperature piezoelectric ceramic material is (1-xy)(BiMe z )FeO3-xPbTiO3-yBaTiO3, wherein Me is a rare earth element, x=0.13~0.27, y=0.10~0.25, z=0~0.30, and z is not 0.

[0009] In some specific embodiments, the Me is selected from any one of La, Ce, Sm, Gd, and Ho.

[0010] The technical solution is to solve the problem that bismuth ferrite-lead titanate-based high-temperature piezoelectric ceramics have a high Curie temperature but a low piezoelectric coefficient. To achieve this purpose, the present invention introduces barium titanate with a perovskite structure to form a ternary solid solution and then dopes the rare earth element Me to obtain a new bismuth ferrite-lead titanate-barium titanate-based high-temperature piezoelectric ceramic material, which can simultaneously obtain a high Curie temperature (>500°C) and enhanced piezoelectric properties, and has broad application prospects in the field of high-temperature piezoelectric ceramic devices.

[0011] In order to further enhance the piezoelectric performance, the rare earth element Me is doped on the basis of the BiFeO3-PbTiO3-BaTiO3 ternary piezoelectric ceramic material. 3+ 、Ce 4+ 、Sm 3+ , Gd 3+ 、Ho 3+ ) is introduced as a high-valent cation to replace the low-valent cation at the A or B position in the ABO3 structure. According to the principle of charge balance, high-valent ion doping will cause a certain number of cation vacancies to appear inside the lattice to maintain electrical neutrality. The formation of cation vacancies is conducive to the flipping of ferroelectric domains and the movement of domain walls, which reduces the coercive field strength of the ceramic and increases the residual polarization strength, making the ceramic easy to polarize. In addition, rare earth ions (La 3+ 、Ce 4+ 、Sm 3 + , Gd 3+ 、Ho 3+ ) may hinder the growth of grains, refine the ceramic grains and improve the density.

[0012] The second technical solution of the present invention is to provide a method for preparing the bismuth ferrite-lead titanate-barium titanate ternary high temperature piezoelectric ceramic material as described in one of the above technical solutions, comprising the following steps:

[0013] S1, according to (1-xy)(BiMe z) FeO3-xPbTiO3-yBaTiO3 stoichiometric ratio is weighed and mixed, wherein x=0.13-0.27, y=0.10-0.25, z=0-0.30, z is not 0, and dried and calcined;

[0014] S2, adding a binder to the mixture after the treatment in step S1, pressing and forming, and obtaining a ceramic blank after debinding treatment;

[0015] S3, sintering the ceramic green body obtained in step S2 to obtain a ceramic sheet, which is a ternary high-temperature piezoelectric ceramic material of bismuth ferrite-lead titanate-barium titanate.

[0016] In some specific embodiments, in step S1, the mixing process conditions are: adding 60%-80% of the total mass of ammonia water and / or ethanol to the raw materials for wet ball milling, the ball mill speed is 150-300 r / min, and the ball milling time is 12-24h.

[0017] The raw materials may be oxides and / or carbonates of Bi, Fe, Pb, Ti, Ba and Me.

[0018] In some specific embodiments, in step S1, the drying temperature is 75-90°C.

[0019] In some specific embodiments, in step S1, the staged calcination includes a first stage calcination and a second stage calcination, wherein the first stage calcination process is: heating to 400-500°C at a heating rate of 4-5°C / min for 2-4h; the second stage calcination process is: heating to 750-850°C at a heating rate of 4-5°C / min for 4-6h.

[0020] In some specific embodiments, in step S1, mixing, drying and calcining are repeated at least once or twice after calcination.

[0021] In some specific embodiments, in step S2, the adhesive is polyvinyl alcohol (PVA), and the amount of the adhesive is 5-10% of the mass of all raw materials.

[0022] In some specific embodiments, in step S2, the process conditions of the debinding treatment are: the debinding temperature is 450-600° C., and the time is 8-24 hours.

[0023] In some specific embodiments, in step S3, the sintering process conditions are: heating to 1020-1080° C. at a heating rate of 4-5° C. / min and sintering for 4-6 hours.

[0024] The prepared bismuth ferrite-lead titanate-barium titanate ternary high-temperature piezoelectric ceramic material was polarized for subsequent testing. The process conditions for polarization were: silver electrodes were plated on the surface of the ceramic sheet, the silver was sintered at 700°C for 10-30 minutes, and then polarized in 100-120°C silicone oil. The polarization DC electric field strength was 3-6kv / mm, and the polarization time was 30-60min.

[0025] The third technical solution of the present invention is to provide an application of the bismuth ferrite-lead titanate-barium titanate ternary high-temperature piezoelectric ceramic material as described in one of the above technical solutions, wherein the bismuth ferrite-lead titanate-barium titanate ternary high-temperature piezoelectric ceramic material is used to prepare sensitive components.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention provides a bismuth ferrite-lead titanate-barium titanate-based high-temperature piezoelectric ceramic material, the chemical composition of which is (1-xy)(BiMe z )FeO3-xPbTiO3-yBaTiO3, wherein Me is a rare earth element, x=0.13~0.27, y=0.10~0.25, z=0~0.30, and z is not 0. In the above-mentioned ternary high-temperature piezoelectric ceramic materials, barium titanate, bismuth ferrite and lead titanate have similar structures, all of which are perovskite structures, and can form a ternary solid solution, adjust the phase boundary, and significantly improve the piezoelectric coefficient of the system. In addition, the rare earth element Me does not have ferroelectric activity. Its addition can weaken the covalent characteristics of the BO bond and promote the rotation of the domain, thereby obtaining excellent piezoelectric properties while ensuring a high Curie temperature, and ion doping reduces leakage conductance, which is beneficial to its application in devices. In summary, the ternary high-temperature piezoelectric material provided by the present invention can meet the use of sensitive components such as high-voltage electric brakes, high-frequency transducers and sensors under high temperature conditions, and has a high practical application value in high-temperature electronic devices.

[0028] (2) The high-temperature piezoelectric ceramic material provided by the present invention can be prepared by a traditional solid-phase reaction method. The preparation process is stable, the operation is simple, the cost is low, and it is suitable for large-scale industrial production. It has practical application value and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The d of the bismuth ferrite-lead titanate-barium titanate high-temperature piezoelectric ceramic material prepared in Example 1 of the present invention and Comparative Example 1 and other high-temperature piezoelectric ceramic materials 33 And Tc performance comparison chart.

[0030] Figure 2 1 and 2 are XRD diffraction patterns of the bismuth ferrite-lead titanate-barium titanate high temperature piezoelectric ceramic materials prepared in Example 1 and Comparative Example 1 of the present invention.

[0031] Figure 3 The scanning electron microscope images and grain size distribution diagrams of the bismuth ferrite-lead titanate-barium titanate high-temperature piezoelectric ceramic materials prepared in Example 1 of the present invention and Comparative Example 1 are shown.

[0032] Figure 4 The dielectric temperature spectra of the bismuth ferrite-lead titanate-barium titanate high-temperature piezoelectric ceramic materials prepared in Example 1 of the present invention and Comparative Example 1 at 1 kHz.

[0033] Figure 5 The bismuth ferrite-lead titanate-barium titanate high temperature piezoelectric ceramic material d prepared in Example 1 of the present invention and Comparative Example 1 33 Temperature variation graph. DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0035] In the following examples and comparative examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0036] Embodiment 1:

[0037] The chemical composition of the preparation in this embodiment is (1-xy)(BiLa z )Bismuth ferrite-lead titanate-barium titanate based piezoelectric ceramics of FeO3-xPbTiO3-yBaTiO3, x=0.23, y=0.15, z=0.01.

[0038] The preparation method of the above-mentioned high temperature piezoelectric ceramic material comprises the following steps:

[0039] (1) Select analytically pure Bi2O3, Fe2O3, PbO, TiO2, BaCO3, and La2O3 as raw material powders and mix them according to the above stoichiometric ratio. Put the raw materials into a ball mill and use anhydrous ethanol as the ball milling medium in an amount of 80% of the total mass of the raw materials. After mixing and ball milling for about 16 hours in a planetary ball mill at a speed of 250 r / min, the discharged materials are placed in a 90° C. oven for rapid drying;

[0040] (2) After drying, the mixed powder is sieved, heated to about 470°C at a heating rate of 5°C / min, and calcined for two hours, and then heated to about 780°C at the same rate and calcined for 4 hours to obtain fine-grained BLF-PT-BT one-calcination synthetic powder;

[0041] (3) The BLF-PT-BT powder calcined once was crushed and ground and placed in a ball mill, and anhydrous ethanol of the same mass ratio (80% of the total mass of the raw materials) was added for a second ball milling for about 10 hours, and the material was dried in an oven at 90°C;

[0042] (4) The powder after the secondary ball milling was heated to about 470°C at a heating rate of 5°C / min and calcined for two hours, and then heated to about 800°C at the same rate and calcined for 4 hours to obtain a secondary calcined BLF-PT-BT powder with fine particles and no impurities;

[0043] (5) crushing and grinding the BLF-PT-BT powder obtained by secondary calcination and putting it into a ball mill, adding anhydrous ethanol of the same mass ratio, and ball milling for three times for about 10 hours, discharging the material and drying it in an oven at 90° C. to obtain BLF-PT-BT ceramic powder;

[0044] (6) Add 5 wt% PVA binder to the BLF-PT-BT powder after three ball milling, grind and granulate, age, and sieve. Then press it into small discs with a pressure of 120 MPa and a diameter of 12 mm and a thickness of 0.8 mm, heat it to 450°C and keep it for 4 h, and then heat it to 600°C and keep it for 4 h to remove organic matter in the ceramic discs;

[0045] (7) Place the debinding small disc into a crucible with powder padding, heat it to about 1040°C in a high-temperature sintering furnace at a heating rate of 5°C / min and keep it at this temperature for 2 hours, then cool it with the furnace;

[0046] (8) grinding both sides of the sintered dense ceramic sample flat, processing it into the required size, and then brushing it with silver and sintering it at 700°C for 30 minutes to obtain a piezoelectric ceramic sample;

[0047] (9) The piezoelectric ceramic sample is placed in silicone oil at 120°C and polarized for 30 min under an electric field of about 3.5 kV / mm to obtain a high-performance bismuth ferrite-lead titanate-barium titanate-based high-temperature piezoelectric ceramic material with the following properties: 33 =256pC / N,k p =0.27,ε r =756, tand=1.21%, Tc=531℃, Q m =59.

[0048] Comparative Example 1

[0049] The chemical composition of the preparation in this embodiment is (1-xy)(BiMe z )FeO3-xPbTiO3-yBaTiO3, x=0.23, y=0.15, z=0 bismuth ferrite-lead titanate-barium titanate based high temperature piezoelectric ceramics.

[0050] The preparation method of the above-mentioned high temperature piezoelectric ceramic material comprises the following steps:

[0051] (1) Select analytically pure Bi2O3, Fe2O3, PbO, TiO2 and BaCO3 as raw material powders and mix them according to the above stoichiometric ratio. Put the raw materials into a ball mill and use anhydrous ethanol as the ball milling medium in an amount of 80% of the total mass of the raw materials. After mixing and ball milling for about 16 hours in a planetary ball mill at a speed of 250 r / min, the discharged materials are placed in a 90°C oven for rapid drying;

[0052] (2) After drying, the mixed powder is sieved and heated to about 470°C at a heating rate of 5°C / min and calcined for two hours, and then heated to about 780°C at the same rate and calcined for 4 hours to obtain fine-grained BF-PT-BT one-calcination synthetic powder;

[0053] (3) The BF-PT-BT powder calcined once was crushed and ground and placed in a ball mill, and anhydrous ethanol of the same mass ratio (80% of the total mass of the raw material) was added for a secondary ball milling for about 10 hours, and the material was discharged and dried in an oven at 90°C;

[0054] (4) The powder after the secondary ball milling was heated to about 470°C at a heating rate of 5°C / min and calcined for two hours, and then heated to about 800°C at the same rate and calcined for 4 hours to obtain a secondary calcined BF-PT-BT powder with fine particles and no impurities;

[0055] (5) The BF-PT-BT powder after secondary calcination was crushed and ground, and then placed in a ball mill, and anhydrous ethanol of the same mass ratio was added, and ball milling was performed three times for about 10 hours, and the material was discharged and dried in an oven at 90°C to obtain BF-PT-BT ceramic powder;

[0056] (6) Add 5 wt% PVA binder to the BF-PT-BT powder after three ball milling, grind and granulate, age, and sieve. Then press it into small discs with a diameter of 12 mm and a thickness of 0.8 mm at a pressure of 120 MPa, heat it to 450°C and keep it for 4 hours, and then heat it to 600°C and keep it for 4 hours to remove organic matter in the ceramic discs;

[0057] (7) Place the debinding small disc into a crucible with powder padding, heat it to about 1040°C in a high-temperature sintering furnace at a heating rate of 5°C / min and keep it at this temperature for 2 hours, then cool it with the furnace;

[0058] (8) grinding both sides of the sintered dense ceramic sample flat, processing it into the required size, and then brushing it with silver and sintering it at 700°C for 30 minutes to obtain a piezoelectric ceramic sample;

[0059] (9) The piezoelectric ceramic sample is placed in silicone oil at 120°C and polarized for 30 min under an electric field of about 3.5 kV / mm to obtain a high-performance bismuth ferrite-lead titanate-barium titanate-based high-temperature piezoelectric ceramic material with the following properties: 33 =208pC / N,k p =0.16,ε r =646, tand=1.11%, Tc=547℃, Q m =91.

[0060] The comparison results are as follows:

[0061] Figure 1 is the d of the BLF-PT-BT high temperature piezoelectric ceramic material prepared in Example 1, Comparative Example 1, and other high temperature piezoelectric ceramic materials (other high temperature piezoelectric ceramic data are from literature). 33 From the Tc performance comparison chart, it can be seen that BLF-PT-BT high temperature piezoelectric ceramic material can have both high Curie temperature (>500℃) and enhanced piezoelectric properties.

[0062] Figure 2 The XRD diffraction patterns of the bismuth ferrite-lead titanate-barium titanate high temperature piezoelectric ceramic materials prepared in Example 1 and Comparative Example 1. By comparing the patterns, it is found that the BLF-PT-BT high temperature piezoelectric ceramic material prepared in Example 1 still maintains a single perovskite structure.

[0063] Figure 3 The scanning electron microscope images and grain size distribution diagrams of the bismuth ferrite-lead titanate-barium titanate high-temperature piezoelectric ceramic materials prepared in Example 1 and Comparative Example 1 show that the average grain size of the BLF-PT-BT high-temperature piezoelectric ceramic in Example 1 is 3.05 μm, while the average grain size of the BF-PT-BT high-temperature piezoelectric ceramic in Comparative Example 1 is larger, at 3.68 μm.

[0064] Figure 4 The dielectric temperature spectra at 1 kHz of the bismuth ferrite-lead titanate-barium titanate high-temperature piezoelectric ceramic materials prepared in Example 1 and Comparative Example 1 show that when the piezoelectric properties of the BLF-PT-BT high-temperature piezoelectric ceramic material are enhanced, its Curie temperature only decreases slightly, but still maintains a high level.

[0065] Figure 5 The bismuth ferrite-lead titanate-barium titanate high temperature piezoelectric ceramic material d prepared in Example 1 of the present invention and Comparative Example 1 33 As shown in the temperature variation diagram, compared with the BF-PT-BT high temperature piezoelectric ceramic material prepared in Comparative Example 1, the BLF-PT-BT ceramic material prepared in Example 1 also has a depolarization temperature of 500°C, and below this temperature, d 33Small variation and good temperature stability.

[0066] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A bismuth ferrite-lead titanate-barium titanate ternary high temperature piezoelectric ceramic material, characterized in that: The general chemical formula of the bismuth ferrite-lead titanate-barium titanate ternary high temperature piezoelectric ceramic material is (1-xy)(BiMe z )FeO3-xPbTiO3-yBaTiO3, wherein Me is a rare earth element, x=0.13~0.27, y=0.10~0.25, z=0~0.30, and z is not 0.

2. The bismuth ferrite-lead titanate-barium titanate ternary high temperature piezoelectric ceramic material according to claim 1, characterized in that: The Me is selected from any one of La, Ce, Sm, Gd and Ho.

3. A method for preparing the bismuth ferrite-lead titanate-barium titanate ternary high temperature piezoelectric ceramic material as claimed in claim 1 or 2, characterized in that: The steps include: S1, according to (1-xy)(BiMe z ) FeO3-xPbTiO3-yBaTiO3 stoichiometric ratio is weighed and mixed, wherein x=0.13-0.27, y=0.10-0.25, z=0-0.30, z is not 0, and dried and calcined; S2, adding a binder to the mixture after the treatment in step S1, pressing and forming, and obtaining a ceramic blank after debinding treatment; S3, sintering the ceramic green body obtained in step S2 to obtain a ceramic sheet, which is a ternary high-temperature piezoelectric ceramic material of bismuth ferrite-lead titanate-barium titanate.

4. The method for preparing the bismuth ferrite-lead titanate-barium titanate ternary high temperature piezoelectric ceramic material according to claim 3, characterized in that: In step S1, the mixing process conditions are: adding ammonia water and / or ethanol in an amount of 60% to 80% of the total mass of the raw materials to the raw materials for wet ball milling, the ball mill speed is 150 to 300 r / min, and the ball milling time is 12 to 24 hours.

5. The method for preparing the bismuth ferrite-lead titanate-barium titanate ternary high temperature piezoelectric ceramic material according to claim 3, characterized in that: In step S1, the staged calcination includes a first stage calcination and a second stage calcination, wherein the first stage calcination process is: heating to 400-500°C at a heating rate of 4-5°C / min for 2-4h; the second stage calcination process is: heating to 750-850°C at a heating rate of 4-5°C / min for 4-6h.

6. The method for preparing the bismuth ferrite-lead titanate-barium titanate ternary high temperature piezoelectric ceramic material according to claim 3, characterized in that: In step S1, after calcination, mixing, drying and calcination are repeated at least once.

7. The method for preparing the bismuth ferrite-lead titanate-barium titanate ternary high temperature piezoelectric ceramic material according to claim 3, characterized in that: In step S2, the adhesive is polyvinyl alcohol, and the amount of the adhesive is 5-10% of the mass of all raw materials.

8. The method for preparing the bismuth ferrite-lead titanate-barium titanate ternary high temperature piezoelectric ceramic material according to claim 3, characterized in that: In step S2, the process conditions of the debinding treatment are: debinding temperature is 450-600°C, and the time is 8-24h.

9. The method for preparing the bismuth ferrite-lead titanate-barium titanate ternary high temperature piezoelectric ceramic material according to claim 3, characterized in that: In step S3, the sintering process conditions are: heating to 1020-1080° C. at a heating rate of 4-5° C. / min and sintering for 4-6 hours.

10. An application of the bismuth ferrite-lead titanate-barium titanate ternary high temperature piezoelectric ceramic material as claimed in claim 1 or 2, characterized in that: The bismuth ferrite-lead titanate-barium titanate ternary high-temperature piezoelectric ceramic material is used for preparing sensitive components.

Citation Information

Patent Citations

  • Ternary piezoelectric material with high curie temperature and preparation method

    CN103467081A

  • Bismuth ferrite-lead titanate-barium titanate ternary-system high-temperature piezoelectric ceramics and preparation method thereof

    CN106810235A

  • Doped and modified bismuth ferrite-lead titanate piezoelectric ceramic and preparation method thereof

    CN107986770A

  • Bismuth ferrite / lead titanate based functional ceramic material and preparation method thereof

    CN112851329A

  • Preparation method of doped bismuth ferrite-barium titanate-based lead-free piezoelectric ceramic material

    CN114180952A